Understanding threats to polio vaccine commitment among caregivers in high-priority areas of Afghanistan: a polling study. Issue 11 (November 2017) - SteelFisher, Gillian K; Blendon, Robert J; Guirguis, Sherine; Lodge, William; Caporello, Hannah; Petit, Vincent; Coleman, Michael; Williams, Matthew R; Parwiz, Sardar Mohammad; Corkum, Melissa; Gardner, Scott; Ben-Porath, Eran N
Summary: Background: Eradication of poliovirus from endemic countries relies on vaccination of children with oral polio vaccine (OPV) many times a year until the age of 5 years. We aimed to determine caregivers' commitment to OPV in districts of Afghanistan at high risk for polio transmission and to examine what knowledge, attitudes, or experiences could threaten commitment. Methods: We designed and analysed a poll using face-to-face interviews among caregivers of children under 5 years of age. The sample was drawn via a stratified multistage cluster design with random route household selection. We calculated the percentage of committed and uncommitted caregivers. All percentages were weighted. We then compared percentages of uncommitted caregivers among those with varying knowledge, attitudes, and experiences, using logistic regression to control for possible demographic confounders. Findings: Between Dec 19, 2014, and Jan 5, 2015, we interviewed 1980 caregivers, 21% of whom were "uncommitted" to accepting OPV. Multiple measures of knowledge, attitudes, and experiences are associated with lack of commitment. For example, compared with their relevant counterparts, caregivers are more likely to be uncommitted if they did not trust vaccinators "a great deal" (54% vs 9%), if they do not know that polio spreads through contaminated water (41% vs 14%), or if they believe rumours that OPV is not halal (50% vs 21%). Interpretation: To enhance OPV commitment, it might be useful to consider a multifactorial approach that highlights building trust in vaccinators, providing facts about transmission, sharing positive messages to overcome key rumours, and strengthening community support for vaccination. Funding: Harvard T H Chan School of Public Health and UNICEF.